Doctor for a day: the impact of a health professions enrichment program on self-efficacy - Celeste Coler; Kareena Patel; A. J. Balatico; Kumhee Ro; Joshua Villarreal; Nora Coronado; Estell Williams (Frontiers in Medicine)
IntroductionHealth profession enrichment programs for underrepresented minority students are crucial to supporting students’ interest in healthcare careers and improving preparedness for important academic and professional milestones. Doctor for a Day, an enrichment program at the University of Washington School of Medicine, hosts monthly events where underrepresented kindergarten-12th grade students are exposed to careers in medicine by healthcare professionals from diverse backgrounds.MethodsThis study investigates to what extent participation in Doctor for a Day programming improves self-efficacy using a survey study of 958 students who attended at least one Doctor for a Day event between 2017 and 2023.ResultsUsing an evaluation tool composed of six questions, our results demonstrate that participation in Doctor for a Day programming increases self-efficacy and interest in medicine as a career. Analysis of these results found significant differences in responses based on grade level, with students in high school demonstrating the largest improvement in self-efficacy.DiscussionThese findings underscore the value of such enrichment programs and offer insights for the development of similar initiatives.